Coregulation of endoplasmic reticulum stress and oxidative stress in neuropathic pain and disinhibition of the spinal nociceptive circuitry. Issue 5 (May 2018) - Ge, Yanhu; Jiao, Yingfu; Li, Peiying; Xiang, Zhenghua; li, Zhi; Wang, Long; Li, Wenqian; Gao, Hao; Shao, Jiayun; Wen, Daxiang; Yu, Weifeng
Abstract : Abstract: The accumulation of unfolded or misfolded proteins in the endoplasmic reticulum (ER) lumen leads to ER stress, which is related to cellular reactive oxygen species production. Neuropathic pain may result from spinal dorsal horn (SDH) ER stress. In this study, we examined the cause–effect relationship between ER stress and neuropathic pain using the spinal nerve ligation (SNL) rat model. We showed that ER stress was mutually promotive with oxidative stress during the process. We also tested the hypothesis that spinal sensitization arose from reduced activities of GABA-ergic interneurons and that spinal sensitization was mediated by SDH ER stress. Other important findings in this study including the following: (1) nociceptive behavior was alleviated in SNL rat as long as tauroursodeoxycholic acid injections were repeated to inhibit ER stress; (2) inducing SDH ER stress in healthy rat resulted in mechanical hyperalgesia; (3) blocking protein disulfide isomerase pharmacologically reduced ER stress and nociceptive behavior in SNL rat; (4) cells in the dorsal horn with elevated ER stress were mainly neurons; and (5) whole-cell recordings made in slide preparations revealed significant inhibition of GABA-ergic interneuron activity in the dorsal horn with ER stress vs in the healthy dorsal horn. Taken together, results of the current study demonstrate that coregulation of ER stress and oxidative stress played an important role in neuropathic pain process. Inhibiting SDH ER stress could be a potential novel strategy to manage neuropathic pain. Abstract : Supplemental Digital Content is Available in the Text.This study demonstrated that endoplasmic reticulum stress was mutually promotive with oxidative stress and led to reduction in activities of inhibitory interneurons in spinal dorsal horn.